Re/creating Entrepreneurs of the Self: Discourses of Worker/Employee ‘Value’ and Current Vocational Rehabilitation Practices - Fadyl, Joanna; McPherson, KM; Nicholls, DA (John Wiley & Sons, 2015)
Vocational rehabilitation for people experiencing work disability is a social practice often situated within health services, but the social and political drivers and effects of this practice are rarely critically analysed in health research or policy. In this study we used a Foucauldian theoretical perspective to analyse the ways in which current vocational rehabilitation practices in New Zealand re/produce notions of worker and employee ‘value’, and how different approaches to vocational rehabilitation deploy current discourses about value. We also consider the subject positions produced through these different approaches and the identities and actions they make possible for people experiencing work disability. The analysis showed that notions about the importance of worker and employee value in a job market are pervasive in vocational rehabilitation, and reflect wider societal discourses. However, the deployment of those discourses in different approaches to vocational rehabilitation practice are diverse, producing different opportunities and constraints for people experiencing disability. We argue that an examination of these various opportunities and constraints at the level of practice approaches is important, as considerable time and resources are allocated to developing solutions to help those who do not thrive in the current systems, yet we rarely critique the premises on which the systems are based.
Keywords: Vocational rehabilitation; Value; Disability; Foucault; Discourse